2010
DOI: 10.1253/circj.cj-09-0899
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Box Isolation on Sympathovagal Balance in Atrial Fibrillation

Abstract: Background: Complete isolation of the posterior left atrium, including all pulmonary veins (box isolation), is a feasible and safe atrial fibrillation (AF) treatment method. Data on long-term effects of box isolation on autonomic function, however, remain limited. Methods and Results:A total of 92 patients (paroxysmal AF, n=76; persistent AF, n=16) undergoing box isolation with non-contact mapping were studied. Twenty-four-hours ambulatory electrocardiograms and transthoracic echocardiography were done at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Multivariate analysis revealed that HF and LF/HF were independent predictors of PAF recurrence. Yamaguchi et al [19] performed box isolation on AF patients, which is a procedure characterized by the complete isolation of four PVs and a larger LA area compared with routine CPVI. After a followup of 16 ± 5 months, significant HRV attenuation was associated with a greater suppression of AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis revealed that HF and LF/HF were independent predictors of PAF recurrence. Yamaguchi et al [19] performed box isolation on AF patients, which is a procedure characterized by the complete isolation of four PVs and a larger LA area compared with routine CPVI. After a followup of 16 ± 5 months, significant HRV attenuation was associated with a greater suppression of AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…PV ectopic foci appear to be at least partially modulated by autonomic signaling, with sympathetic stimulation with isoproterenol being frequently utilized to “bring out” these triggers in patients undergoing ablation for AF. Clinical studies have demonstrated a change in heart rate variability after PV ablation 25 . Several investigators have also noted Bezold-Jarisch-like or ‘vagal’ reflexes during radiofrequency ablation of the PVs.…”
Section: Autonomic Profile Of the Pvs And Pla And Its Relationship Tomentioning
confidence: 99%
“…As alluded to earlier, much of the data supporting the involvement of the autonomic nervous system in patients with AF comes from noninvasive measures of autonomic tone such as heart rate variability (HRV) 25 . It must be remembered, however, that HRV is a measure of autonomic modulation on the sinus node, and does not reliably quantify sympathetic and parasympathetic activity.…”
Section: Recent Developments In Imaging Of the Autonomic Innervation mentioning
confidence: 99%
“…Furthermore, parasympathetic denervation may have contributed to a decrease in CFAE areas. Since parasympathetic fibers and muscarinic receptors are preferentially located in the posterior wall of the left atrium, LAPWI attenuates parasympathetic nerve activities and increases sympathovagal balance . Parasympathetic activity causes the release of acetylcholine, which acts predominantly on M2 receptors to activate the G‐protein‐activated potassium current (I KACh ) and shorten the duration of the action potential and effective refractory period .…”
Section: Discussionmentioning
confidence: 99%